Conditional conservatism and labor investment efficiency. Issue 2 (August 2018) - Ha, Joohyung; Feng, Mingming
Abstract: Prior literature documents that asymmetric timely recognition of losses versus gains (also known as conditional conservatism) can induce management to make more efficient investment decisions by mitigating information asymmetry between management and investors and providing early signals about the profitability of projects that are undertaken. In this paper, we investigate the impact of conservatism on an important investment decision that has been overlooked, namely, investment in labor. We find that conservatism is negatively associated with labor investment inefficiency; more specifically, conservatism reduces inefficient investment practices on the labor market, including over-hiring, under-firing, under-hiring, and over-firing. Our results hold after controlling for managerial ability, corporate governance, and other investments.